2008
DOI: 10.1007/s11060-008-9700-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated stereotactic radiotherapy in combination with whole brain radiotherapy for brain metastases

Abstract: Background The efficacy and toxicity of hypofractionated stereotactic radiotherapy (HSRT) in combination with whole brain radiotherapy (WBRT), for the treatment of 1-4 brain metastases, using a non invasive fixation of the skull, was investigated. Methods Between 04/2001 and 01/2006 30 patients with 44 brain metastases underwent irradiation. Every patient received WBRT (10 9 3 Gy); 41/44 lesions received HSRT boost with a median dose fraction of 6 Gy, the fractionation schemes were 3 9 6 Gy and 4 9 8 Gy; a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…It has been reported that median survivals were 6.5-16 months following WBRT plus focal radiotherapy boost in patients with single intracranial lesion, corresponding to 5.8-13months in patients with multiple intracranial lesions [8,9,16,17]. Similarly, patients with number of lesions <3 showed better outcomes in our study, and the median survival was comparable to the data reported by other investigators [11,17,20]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It has been reported that median survivals were 6.5-16 months following WBRT plus focal radiotherapy boost in patients with single intracranial lesion, corresponding to 5.8-13months in patients with multiple intracranial lesions [8,9,16,17]. Similarly, patients with number of lesions <3 showed better outcomes in our study, and the median survival was comparable to the data reported by other investigators [11,17,20]. …”
Section: Discussionsupporting
confidence: 87%
“…The reported one-year ICR and median survivals of patients with limited brain metastases received WBRT plus sequential focal hfSRT boost were 66%-86% and 7.5-13 months [16-20]. Unlike reports above, approximately half of patients in our study had multiple (≥3) or large (≥3 cc) intracranial lesions, which were always excluded in other studies.…”
Section: Discussionmentioning
confidence: 62%
“…Fractionated administration of radiation dose potentially decreases toxicity to late-responding normal tissues compared to a single acute dose of radiation for a given level of tumor damage [23], and reoxygenation and redistribution of the cell cycle between fractions render hypoxic tumor cells and cells in a lessresponding cell cycle more radiosensitive [9,16]. As expected from this concept, recently published studies on fractionated SRS for large BMs have demonstrated high LTC rates ranging from 63 to 100 % at 1 year with acceptable risks of toxicity [4,5,8,10,11,13,14,21,22]. Along with these, in the present study, the LTC rate was 87.0 % at 1 year and the median OS was 16 months in patients with large BMs treated with fractionated CK, which also compares well with the outcomes of single-fraction SRS for small BMs [6,17,26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the concept of fractionated SRS has been emerging and is reportedly effective and safe in treating BMs, especially large ones [4,5,8,10,11,13,14,21,22]. The Cyberknife (CK) (Accuray, Sunnyvale, CA, USA) features a more flexible fractionation delivery of SRS compared with GK, as it relies on the frameless, image-guided technology for tracking the target both in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…For lesions larger than 10 mL, precise delineation of the margin is also important because it may be necessary to reduce the dose to control damage to the surrounding tissue. 10,11 One limitation of the current study is the histological nature of the area in which the double-dose study can't depicted. Histologically, a typical metastatic brain tumor shows clear margins surrounded by gliosis of one-mm thickness, 12,13 so the approximately one-mm difference between the diameters we measured during the early and late phases of enhancement may correspond with gliosis surrounding the tumor margin.…”
Section: Discussionmentioning
confidence: 96%